KINERJA KEUANGAN PT BLUE BIRD TBK - Viraisya Haninda Drana Wasistha; Deni Herdiyana (Jurnal Manajemen Bisnis Krisnadwipayana, 2021)
This research was conducted to analyze the financial performance of PT Blue Bird Tbk based on financial ratios consisting of liquidity ratios, solvency, activity, and profitability. The research method used is through a quantitative approach. To support this research, data methods were carried out which included literature study and data analysis. The results of the study can be concluded that the liquidity and solvency ratio of PT Blue Bird Tbk is quite good. However, the company's activity and profitability ratios show a poor rating compared to the industry average